Gorki e a engenharia da alma: o herói positivo e o novo homem soviético em A mãe - Marcelo Dourado de Campos (2019)
The following research aims to discuss the role of the life and work of Maxim Gorky in building the culture of the stalinist regime. Placed at the top of the socialist literary hierarchy, the writers ouvre provides the link between the utopian yearnings of late nineteenth century Russian intellectuals and the establishment of the new Soviet literature. In Mother (1907), Gorky´s novel widely celebrated by the stalinist cultural apparatus, the literary patterns of the new aesthetics are expressed at their embryonic stage, later to be developed into what the Soviet regime will deem mankind´s ultimate literary achievement: Socialist Realism. At the core of the novel´s narrative lies the key component of the new literary aesthetic: the positive hero. In a socialist realist plot, the narrative arc of the hero enacts, in the individual sphere, the journey by which the human spirit must travel in order to bring about, in history, the socialist utopia from spontaneity to absolute consciousness. We argue that through the positive hero, the role model, the ideal revolutionary, Gorky not only updates the utilitary and normative aspects of Russian radical literature, but also foresees the essential elements to the forging of the stalinist view of reality, whose totalitarian nature will determine it as an order of being in which Soviet society (and humankind) is empowered to shape itself into its superior version The New Soviet Men. Through the analysis of the main elements in Mother that are reproduced and iterated in the later socialist realist body of work, it is possible to pinpoint the deepest layers of intellectual thought that would eventually sustain the Soviet literary aesthetics as an accurate expression of the stalinist image of reality which presents itself, at the least, as an ideological filter and at the most, as a surrogate for the experience of reality. Once in it, the writer becomes an engineer of souls, spearheading the process of utopian fulfillment of human capacities, in a society where the notions of present and future are merged together. The Soviet citzen, caught in between the official reality and individual experience, lives in an uncertain state amidst what it is and what it should be.